Analyses of technical and tactical data in attack and defense at high level handball teams - Molfetas, A.; Hatzimanouil, D.; Papadopoulou, Z.; Skandalis, V.; Vrabas, S. I. (Journal of Physical Education and Sport, 2019)
Measurement of performance plays an important role in planning the training and to prepare the game plan. The analysis after a game helps to evaluate the performance, while mass analysis after one season, can contribute to evaluate the failure or the success of the participating teams. The purpose of this study was to record and process data from high-level handball competitions of the Greek handball championships of the 2017-2018 season. The sample were consisted of 60 handball matches. The variables evaluated were: a) attack variables (6m throws, 6m goals, 9m throws, 9m goals, penalty throws, counterattacks, quick throw-off), b) defense variables (goalie`s saves, defense blocks), c) the variables of the inability of the attack or the defensive ability, leading to attack errors (offensive fouls, steps, 3'' errors, passing errors, ball steals), e) the result of the matches (win, draw, defeat). SPSS 22 statistical program was utilized for the analysis of the results and the method applied was descriptive and inferential statistics. Mann-Whitney U test was used to compare differences between home and visitor teams and between winning and defeated teams. In most of the variables home teams had better values than visitor teams. In all variables winning teams had better values than defeated teams except 9m. throws. Mann-Whitney U test showed no statistically significant difference concerning home and visitor teams except counterattacks (p = 0.012). Between the winning and defeated teams there was a significant difference in 6m. throws (p = 0.000), 6m. goals (p = 0.000), counterattacks (p = 0.002), goalie`s saves (p = 0.004), defensive blocks (p = 0.006), "steps" - 3'' errors (p = 0.047), passing errors (p = 0.003) and in ball steals (p = 0.001). It is concluded that Greek Championship handball matches are sometimes similar and sometimes different comparing to the foreign championship matches.